2014
DOI: 10.18632/genesandcancer.23
|View full text |Cite
|
Sign up to set email alerts
|

CD133-positive cancer stem cells from colo205 human colon adenocarcinoma cell line show resistance to chemotherapy and display a specific metabolomic profile

Abstract: During the past decade, cancer stem-like cells (CSCs) have drawn substantial interest in cancer research since they have been described as major targets to improve treatment of tumors and to prevent recurrence and metastasis. In this paper, we report on the search for CSCs within the Colo205 human adenocarcinoma cell line. We describe that CD133 (prominin) was the only reliable marker for the isolation and characterization of CSCs within a Colo205 cell population. CD133-positive cells displayed many CSC charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
2
32
0
1
Order By: Relevance
“…It was found that CD133+ cells could grow tumors in all three xenografted NOD-SCID mice with 1.5 × 10 5 cells but not CD133- cells. This finding is consistent with previous reports on colon cancer 49 and glioblastoma multiforme 50 . CSCs were found in CD133+ fractions of EC.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that CD133+ cells could grow tumors in all three xenografted NOD-SCID mice with 1.5 × 10 5 cells but not CD133- cells. This finding is consistent with previous reports on colon cancer 49 and glioblastoma multiforme 50 . CSCs were found in CD133+ fractions of EC.…”
Section: Discussionsupporting
confidence: 94%
“…CD133 was recently reported as a promising CSC marker noted in prostate cancer ( 35 37 ), brain tumours ( 38 – 41 ), colon cancer ( 42 44 ) and hepatic carcinoma ( 45 48 ). However, in the context of lung cancer stem cells, the utility of the marker appears limited due to the low expression detected in most lung cancer samples ( 49 , 50 ), and the discrepancy of the findings in regards to CD133 in most studies have questioned the prognostic value of this marker in clinical application ( 50 52 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date metabolomics has rarely been exploited to study cancer stem cells. To our knowledge, the only reported applications of metabolomics in this context was its use to study the differences between tumors derived from fresh glioma stem cells and cultured glioma stem cells in vivo using nuclear magnetic resonance spectroscopy [ 16 ], a recently published report on breast cancer stem cells’ reliance on glycolysis [ 17 ], and recent isolation of a colon cancer stem cell line with metabolomic characterization [ 18 ]. There is also increasing recent interest in cancer stem cell metabolism through approaches other than metabolomics, with many of the discoveries focused on enhanced glycolysis [ 19 30 ].…”
Section: Introductionmentioning
confidence: 99%